Analysis of the Effect of Local Taxpayer Service and Awareness on Compliance in Paying Building Permit Fees Through Satisfaction as an Intervening Variable - Diah Purwani Susanti; H.Mochamad Edris; Mamik Indaryani (Journal of Finance and Business Digital, 2023)
This study aims to analyze the effect of service and awareness of local taxpayers on compliance with building permit fees through satisfaction as an intervening variable. The sampling technique used in this study was proportional random sampling. The collection method uses a questionnaire. The sources and types of this research are primary data and secondary data. Conclusion There is a positive and significant effect of Local Taxpayer Awareness on Satisfaction, Satisfaction provides added value in mediating the effect of Services on Compliance Paying Building Permit Fees at the Investment Service and One Stop Integrated Service in Pati Regency, Satisfaction provides added value in mediating Regional Taxpayer Awareness Compliance with Paying Building Permit Fees at the Investment and One-Stop Service Office of Pati Regency.